Environmentally friendly epoxy-based thin-layer overlay packaging composition and method for constructing thin-layer overlay packaging using the same

KR103018576B1Active Publication Date: 2026-09-11SAMSIN ENTERPRISE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020250101072
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2026-09-11
Estimated Expiration
2045-07-25

Smart Images

  • Figure 112025084621776-PAT00008_ABST
    Figure 112025084621776-PAT00008_ABST
Patent Text Reader

Abstract

The present invention relates to an environmentally friendly epoxy-based thin-layer overlay paving material composition and a method for constructing a thin-layer overlay paving material using the same. Specifically, the environmentally friendly epoxy-based thin-layer overlay paving material composition comprises: 1) 40 to 80 weight% of an epoxy main component containing 100 parts by weight of a base resin containing an epoxy resin; 10 to 50 parts by weight of castor oil glycidyl ether; 1 to 20 parts by weight of an aliphatic epoxy resin; 1 to 10 parts by weight of D-erythro-sphingosine; and 1 to 10 parts by weight of cordycepin represented by the following chemical formula 1; and 2) 100 parts by weight of di(4-aminocyclohexylmethyl)aniline; and 10 to 30 parts by weight of a dihydrazide compound which is adipic acid dihydrazide, isophthalic acid dihydrazide, or a mixture thereof. It comprises 20 to 60 weight% of an epoxy curing agent containing 1 to 10 parts by weight of N,N-bis(2,3-epoxypropyl)-o-toluidine; 1 to 10 parts by weight of N,N'-bis(salicylidene)-1,3-propanediamine; and 1 to 10 parts by weight of microcrystalline wax. This environmentally friendly epoxy-based thin-layer overlay paving material composition and the construction method of the thin-layer overlay paving material using it use an epoxy main component composed of ingredients harmless to the human body, suppresses the generation of concrete waste caused by cutting the existing paving layer, is semi-permanent and environmentally friendly, induces integrated behavior between the existing paving layer and the overlay layer, and has excellent adhesion and elasticity so that it can be strongly bonded to the existing paving layer regardless of the behavior of the existing paving layer due to temperature and environmental changes, and has the effect of improving durability such as waterproofness, abrasion resistance, freeze-thaw resistance, wear resistance, and slip resistance. [Chemical Formula 1]
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an environmentally friendly epoxy-based thin-layer overlay paving material composition that uses an epoxy base composed of components harmless to the human body, suppresses the generation of concrete waste caused by cutting the existing paving layer, is semi-permanent and environmentally friendly, induces integrated behavior between the existing paving layer and the overlay layer, has excellent adhesion and elasticity so that it can be strongly adhered to the existing paving layer regardless of the behavior of the existing paving layer due to temperature and environmental changes, and improves durability such as waterproofness, abrasion resistance, freeze-thaw resistance, wear resistance, and slip resistance, and a method for constructing a thin-layer overlay paving material using the same. Background Technology

[0003] Paved roads are damaged by factors such as impact from continuous traffic loads, various chemical erosion, and other weather conditions, so regular maintenance work is required to extend their lifespan.

[0004] Generally, the cut-overlay method, which involves cutting the existing pavement surface and pouring a repair asphalt concrete composition, is applied as a repair method for asphalt paved roads.

[0005] While this overlay method has the advantages of being easy to construct and providing a pleasant road pavement by forming a new surface layer structure, it causes traffic congestion during construction, and there is a concern that a significant amount of maintenance budget will be wasted by applying asphalt milling overlays to some roads, even though they are structurally stable.

[0006] Furthermore, as the rate of increase in the lifespan of paved roads gradually decreases when the overlay method is repeatedly performed—such as when the first overlay increases the lifespan by about 5 years, when the second overlay increases it by about 3 to 4 years, and when the third overlay increases it by about 3 years—not only is the maintenance cycle of paved roads becoming increasingly shortened, but the issues of waste disposal costs and disposal sites for excavated waste asphalt are also serious.

[0007] Accordingly, a thin-layer overlay paving method for preventive repair has been developed, which can improve the performance of paved roads, such as anti-slip, improved visibility, and noise reduction, and theoretically extend the service life by about 10 to 15 years by applying a thin-layer overlay paving material containing aggregates and polymer resins without cutting off the entire surface of the road pavement.

[0008] The above thin-layer overlay paving is formed as a paving material (film) for paving crosswalks, etc. using a paint containing solvent-based resins such as epoxy, acrylic, or urethane as a binder, or it is also used to prevent slippage of moving vehicles by applying a binder to the road and then sprinkling fine aggregate of friction materials (silica sand, sand, steel slag, etc.) for anti-slip purposes to fix them to the binder.

[0009] However, the resins conventionally used in thin-layer overlay pavements had several disadvantages: insufficient adhesion to the existing road surface, a high risk of damage due to differences in behavior, and a lack of flexibility leading to cracking and detachment; furthermore, if the anti-slip friction material detaches, slip resistance rapidly decreases, drastically shortening the pavement's lifespan. Additionally, there was the disadvantage of excessively long construction times due to slow curing depending on the weather. Prior art literature

[0011] Republic of Korea Registered Patent No. 10-2667546 Republic of Korea Registered Patent No. 10-2351716 Republic of Korea Registered Patent No. 10-2678845 The problem to be solved

[0012] The present invention was devised to solve the aforementioned problems, and one embodiment of the present invention aims to provide an environmentally friendly epoxy-based thin-layer overlay paving material composition and a method for constructing a thin-layer overlay paving material using the same, which suppresses the generation of concrete waste caused by cutting the existing pavement layer, has excellent adhesion to the existing pavement road surface, can secure integrated behavioral characteristics between the existing pavement layer and the overlay layer, and has excellent inherent durability and elasticity such as waterproofing, abrasion resistance, and freeze-thaw resistance, thereby improving the durability life of the pavement road by applying it to preventive repair of the pavement road.

[0013] The various problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0015] One embodiment of the present invention comprises: 1) 40 to 80 weight% of an epoxy main component containing 100 weight parts of a base resin containing an epoxy resin; 10 to 50 weight parts of castor oil glycidyl ether; 1 to 20 weight parts of an aliphatic epoxy resin; 1 to 10 weight parts of D-erythro-sphingosine; and 1 to 10 weight parts of cordycepin represented by the following chemical formula 1; and 2) 100 weight parts of di(4-aminocyclohexylmethyl)aniline; 10 to 30 weight parts of a dihydrazide compound which is adipic acid dihydrazide, isophthalic acid dihydrazide, or a mixture thereof; and 1 to 10 weight parts of N,N-bis(2,3-epoxypropyl)-o-toluidine. The present invention provides an environmentally friendly epoxy-based thin-layer overlay packaging composition comprising 20 to 60 weight% of an epoxy curing agent containing 1 to 10 weight parts of N,N'-bis(salicylidene)-1,3-propanediamine and 1 to 10 weight parts of microcrystalline wax.

[0016] [Chemical Formula 1]

[0017]

[0018] The base resin containing the above epoxy resin is

[0019] A mixture comprising a bisphenol F-type epoxy resin and a methacrylate compound having three or more functional groups mixed in a weight ratio of 1:0.1 to 0.3;

[0020] The above methacrylate compounds with three or more functional groups may be one or more selected from the group consisting of trimethylolpropane methacrylate, pentaerythritol trimethacrylate, and pentaerythritol tetramethacrylate.

[0021] The above microcrystalline wax is

[0022] It is a microcrystalline wax treated with kelp extract;

[0023] The microcrystalline wax treated with the above kelp extract may be prepared by a method comprising the steps of: preparing raw kelp from which sodium has been removed by immersing raw kelp in washing water at 6 to 8 ℃ for 3 to 5 hours; preparing roasted kelp by roasting the raw kelp from which sodium has been removed at 80 to 90 ℃ for 30 to 50 seconds; and preparing microcrystalline wax treated with the kelp extract by mixing 100 parts by weight of the roasted kelp, 30 to 50 parts by weight of microcrystalline wax, and 500 to 5000 parts by weight of a water solvent, and extracting under conditions of ultrasonic intensity of 500 to 2000 W, stirring speed of 20 to 100 rpm, and temperature of 1 to 20 ℃.

[0024] The above solvent is

[0025] It may be a mixed solvent in which water, magnetized water and marrubiin of Formula 2 are mixed in a weight ratio of 1:0.5 to 1:0.1 to 0.3.

[0026] [Chemical Formula 2]

[0027]

[0028] In addition, another embodiment of the present invention provides a thin-layer overlay paving construction method comprising: a pretreatment step for removing foreign substances from a substrate surface; a pouring step for forming an adhesive layer by pouring an environmentally friendly epoxy-based thin-layer overlay paving material composition onto the substrate surface after the pretreatment step; a laying step for forming an aggregate layer by laying aggregate on the surface after the pouring step; a first curing step for curing the substrate surface after the laying step; an aggregate removal step for removing excess aggregate from the substrate surface after the first curing step; and a second curing step for curing the substrate surface after the aggregate removal step. Effects of the invention

[0030] An environmentally friendly epoxy-based thin-layer overlay paving material composition according to one embodiment of the present invention and a method for constructing a thin-layer overlay paving material using the same use an epoxy main component composed of ingredients harmless to the human body and suppress the generation of concrete waste caused by cutting the existing paving layer, thereby having the effect of being semi-permanent and environmentally friendly.

[0031] In addition, the environmentally friendly epoxy-based thin-layer overlay paving material composition according to one embodiment of the present invention and the construction method of the thin-layer overlay paving material using the same improve the penetration of the paving material composition into the existing paving layer to induce integrated behavior between the existing paving layer and the overlay layer, and has excellent adhesion and flexibility, so it can be strongly adhered to the existing paving layer regardless of the behavior of the existing paving layer due to temperature and environmental changes, and has the effect of improving durability such as water resistance, abrasion resistance, freeze-thaw resistance, wear resistance, and slip resistance. Brief explanation of the drawing

[0033] FIG. 1 illustrates a thin-layer overlay paving construction method using an environmentally friendly epoxy-based thin-layer overlay paving material composition according to one embodiment of the present invention. Specific details for implementing the invention

[0034] Hereinafter, embodiments of the present invention will be described in detail. However, these are presented as examples and are not intended to limit the present invention, and the present invention is defined only by the scope of the claims set forth below.

[0035] One embodiment of the present invention comprises: 1) 40 to 80 weight% of an epoxy main component containing 100 weight parts of a base resin containing an epoxy resin; 10 to 50 weight parts of castor oil glycidyl ether; 1 to 20 weight parts of an aliphatic epoxy resin; 1 to 10 weight parts of D-erythro-sphingosine; and 1 to 10 weight parts of cordycepin represented by the following chemical formula 1; and 2) 100 weight parts of di(4-aminocyclohexylmethyl)aniline; 10 to 30 weight parts of a dihydrazide compound which is adipic acid dihydrazide, isophthalic acid dihydrazide, or a mixture thereof; and 1 to 10 weight parts of N,N-bis(2,3-epoxypropyl)-o-toluidine. The present invention provides an environmentally friendly epoxy-based thin-layer overlay packaging composition comprising 20 to 60 weight% of an epoxy curing agent containing 1 to 10 weight parts of N,N'-bis(salicylidene)-1,3-propanediamine and 1 to 10 weight parts of microcrystalline wax.

[0036] [Chemical Formula 1]

[0037]

[0038] An environmentally friendly epoxy-based thin-layer overlay paving material composition and a construction method for a thin-layer overlay paving material using the same according to one embodiment of the present invention use an epoxy main component composed of ingredients harmless to the human body and suppress the generation of concrete waste caused by cutting the existing paving layer, thereby having the effect of being semi-permanent and environmentally friendly. In addition, an environmentally friendly epoxy-based thin-layer overlay paving material composition and a construction method for a thin-layer overlay paving material using the same according to one embodiment of the present invention improve the penetration of the paving material composition into the existing paving layer, thereby inducing integrated behavior between the existing paving layer and the overlay layer, and has excellent adhesion and flexibility, allowing it to be strongly adhered to the existing paving layer regardless of the behavior of the existing paving layer due to temperature and environmental changes, and has the effect of improving durability such as water resistance, abrasion resistance, freeze-thaw resistance, wear resistance, and slip resistance.

[0039] Hereinafter, the environmentally friendly epoxy-based thin-layer overlay packaging material composition according to the present invention will be described in more detail as follows.

[0040] An environmentally friendly epoxy-based thin-layer overlay packaging material composition according to one embodiment of the present invention comprises 40 to 80 weight% of an epoxy main component and 20 to 60 weight% of an epoxy curing agent, which can achieve the effects of the present invention as described above.

[0041] Specifically, the above epoxy main component contains 100 parts by weight of a base resin containing an epoxy resin; 10 to 50 parts by weight of castor oil glycidyl ether; 1 to 20 parts by weight of an aliphatic epoxy resin; 1 to 10 parts by weight of D-erythro-sphingosine; and 1 to 10 parts by weight of cordycepin represented by the following chemical formula 1.

[0042] The base resin containing the above epoxy resin serves to improve strength, chemical resistance, reactivity, corrosion resistance, and flowability.

[0043] The above epoxy resin is not specifically limited to those generally used in the field, but it is preferable to use an eco-friendly and harmless bisphenol F type epoxy resin.

[0044] In addition, the above base resin may be used with an additional mixture of a (meth)acrylate compound to improve adhesion to the substrate and flexibility, along with the above effects, and to suppress the risk of cracking and breakage even when exposed to low temperatures.

[0045] The above (meth)acrylate compound is not specifically limited to those generally used in the field, but it is preferable to use a methacrylate compound with three or more functional groups that provides high curing speed, crosslinking density and hardness, and has scratch resistance. The above methacrylate compound with three or more functional groups may be, for example, one or more selected from the group consisting of trimethylolpropane methacrylate, pentaerythritol trimethacrylate, and pentaerythritol tetramethacrylate.

[0046] For this base resin, it is preferable that a bisphenol F type epoxy resin and a trifunctional or higher methacrylate compound are mixed in a weight ratio of 1:0.1 to 0.3 in terms of curing speed, viscosity, and hardness.

[0047] Hereinafter, the content of other components constituting the above epoxy main component is based on 100 parts by weight of a base resin containing the above epoxy resin (hereinafter referred to as 'base resin').

[0048] The above castor oil glycidyl ether provides excellent flexibility, such as tensile strength and elongation, and plays a role in inducing integrated behavior between the existing paving layer and the thin overlay layer, with minimal shrinkage deformation upon curing.

[0049] It is preferable that such castor oil glycidyl ether be contained in a range of 10 to 50 parts by weight per 100 parts by weight of the base resin. If the content of the aliphatic epoxy resin is too low, there is a problem that the improvement effect described above may be insufficient, and if the amount of the castor oil glycidyl ether is too high, there is a problem that low-temperature curing performance may be reduced.

[0050] The above-mentioned aliphatic epoxy resin serves to reduce viscosity and improve flexibility, and is a material obtained by epoxidation using an aliphatic alcohol and epichlorohydrin. For example, it may be one or more selected from the group consisting of glycerol diglycidyl ether, carboxylic acid glycidyl ether, butyl glycidyl ether, poly(propylene glycol) diglycidyl ether, and neopentyl diglycidyl ether. Preferably, it is better to use a mixture of glycerol diglycidyl ether and carboxylic acid glycidyl ether in a weight ratio of 1:1.

[0051] It is preferable that such aliphatic epoxy resin be contained in a range of 1 to 20 parts by weight per 100 parts by weight of the base resin. If the content of the aliphatic epoxy resin is too low, there is a problem that the viscosity is high, which may reduce workability and flexibility on site, and if the content of the aliphatic epoxy resin is too high, there is a problem that physical properties such as tensile strength and hardness may be reduced.

[0052] The above-mentioned D-erythro-sphingosine not only improves dispersibility and prevents clumping from occurring again even after mixing the composition, but also improves adhesion durability by enhancing the bonding strength with the pavement surface and aggregate. In addition, it plays a role in suppressing the increase in viscosity caused by the base resin.

[0053] It is preferable that such D-erythro-sphingosine be contained in a range of 1 to 10 parts by weight per 100 parts by weight of the base resin. If the content of D-erythro-sphingosine is too low, there is a problem that the improvement effect described above may be insufficient, and if the content of D-erythro-sphingosine is too high, there is a problem that durability and flexibility may be reduced.

[0054] Cordycepin, represented by the above chemical formula 1, plays a role in preventing aging and delamination of packaging materials and improving crack resistance. In addition, it plays a role in reducing and improving heat resistance and yellowing caused by ultraviolet rays, and providing thermal stability.

[0055] It is preferable that such cordycepin be contained in a range of 1 to 10 parts by weight per 100 parts by weight of the base resin. If the cordycepin content is too low, there is a problem that the improvement effect described above may be insufficient, and if the cordycepin content is too high, there is a problem that wear resistance and weather resistance may be reduced.

[0056] The present invention uses an epoxy curing agent to cure the epoxy main component. It is preferable that the epoxy curing agent be contained in an amount of 20 to 60 weight percent with respect to the environmentally friendly epoxy-based thin-layer overlay packaging material composition of the present invention. If the content of the epoxy curing agent is too low, the curing efficiency of the main component may decrease, which may lead to a problem of reduced physical properties or workability; if the content of the epoxy curing agent is too high, there may be a problem where physical properties such as adhesion may become poor due to excessive free radicals of the epoxy curing agent present in the environmentally friendly epoxy-based thin-layer overlay packaging material composition.

[0057] The above epoxy curing agent contains 100 parts by weight of di(4-aminocyclohexylmethyl)aniline; 10 to 30 parts by weight of a dihydrazide compound which is adipic acid dihydrazide, isophthalic acid dihydrazide, or a mixture thereof; 1 to 10 parts by weight of N,N-bis(2,3-epoxypropyl)-o-toluidine; 1 to 10 parts by weight of N,N'-bis(salicylidene)-1,3-propanediamine; and 1 to 10 parts by weight of microcrystalline wax.

[0058] The above-mentioned di(4-aminocyclohexylmethyl)aniline serves to cure the epoxy base material, thereby imparting excellent mechanical properties, tensile strength, flexibility, high elongation, chemical resistance, water resistance, rust prevention, and salt penetration resistance.

[0059] The content of other components constituting the above epoxy curing agent is based on 100 parts by weight of the above di(4-aminocyclohexylmethyl)aniline.

[0060] The above dihydrazide compound serves to control low-temperature curing, pot life, and curing time, and to improve curing reactivity. It also provides adhesive strength, water resistance, corrosion resistance, salt penetration resistance, and water resistance, and offers high fluidity to enable the formation of thin layers.

[0061] The above dihydrazide compound may be adipic acid dihydrazide, isophthalic acid dihydrazide, or a mixture thereof, and in terms of efficiency in improving reactivity, it is preferable to use a mixture of adipic acid dihydrazide and isophthalic acid dihydrazide in a weight ratio of 1:1.

[0062] It is preferable that such dihydrazide compounds be contained in a range of 10 to 30 parts by weight per 100 parts by weight of di(4-aminocyclohexylmethyl)aniline. If the content of the dihydrazide compound is too low, there is a problem that the above-mentioned improvement effect may be insufficient, and if the content of the dihydrazide compound is too high, there is a problem that tensile strength and hardness may decrease.

[0063] The above N,N-bis(2,3-epoxypropyl)-o-toluidine serves to improve adhesion and impart wear resistance, chemical resistance, rust prevention, thermal compatibility, low-temperature curing ability, and weather resistance.

[0064] It is preferable that such N,N-bis(2,3-epoxypropyl)-o-toluidine be contained in a range of 1 to 10 parts by weight per 100 parts by weight of di(4-aminocyclohexylmethyl)aniline. If the content of N,N-bis(2,3-epoxypropyl)-o-toluidine is too low, there is a problem that the above-mentioned improvement effect may be insufficient, and if the content of N,N-bis(2,3-epoxypropyl)-o-toluidine is too high, there is a problem that flexibility may be reduced.

[0065] The above N,N'-bis(salicylidene)-1,3-propanediamine plays a role in improving rapid curing performance and tensile strength while simultaneously enhancing excellent rust prevention and freeze-thaw resistance.

[0066] It is preferable that such N,N'-bis(salicylidene)-1,3-propanediamine be contained in a range of 1 to 10 parts by weight per 100 parts by weight of di(4-aminocyclohexylmethyl)aniline. If the content of N,N'-bis(salicylidene)-1,3-propanediamine is too low, there is a problem that the above-mentioned improvement effect may be insufficient, and if the content of N,N'-bis(salicylidene)-1,3-propanediamine is too high, there is a problem that weather resistance may be reduced.

[0067] The above microcrystalline wax improves wear resistance, plasticity, and water retention, and serves to prevent cracking and enhance strength.

[0068] In addition, to enhance viscosity and adhesion as well as the above roles, microcrystalline wax treated with kelp extract may be used. Specifically, the microcrystalline wax treated with kelp extract may be prepared by a method comprising the steps of: preparing raw kelp from which sodium has been removed by immersing raw kelp in washing water at 6 to 8°C for 3 to 5 hours; preparing roasted kelp by roasting the raw kelp from which sodium has been removed at 80 to 90°C for 30 to 50 seconds; and preparing microcrystalline wax treated with kelp extract by mixing 100 parts by weight of the roasted kelp, 30 to 50 parts by weight of microcrystalline wax, and 500 to 5000 parts by weight of a water solvent, and extracting under conditions of ultrasonic intensity of 500 to 2000 W, stirring speed of 20 to 100 rpm, and temperature of 1 to 20°C.

[0069] In addition, the above ultrasonic extraction may use a mixed solvent in which water, magnetized water, and marrubiin of Formula 2 are mixed in a weight ratio of 1:0.5 to 1:0.1 to 0.3. The magnetized water and marrubiin of Formula 2 have excellent extraction efficiency and simultaneously improve adhesion durability by enhancing the penetration of the packaging material composition into the existing packaging layer.

[0070] [Chemical Formula 2]

[0071]

[0072] It is preferable that such microcrystalline wax be contained in a range of 1 to 10 parts by weight per 100 parts by weight of di(4-aminocyclohexylmethyl)aniline. If the content of the microcrystalline wax is too low, there is a problem that the improvement effect described above may be insufficient, and if the content of the microcrystalline wax is too high, there is a problem that the strength may be reduced.

[0073] Meanwhile, FIG. 1 illustrates a thin-layer overlay paving construction method using an environmentally friendly epoxy-based thin-layer overlay paving material composition according to one embodiment of the present invention.

[0074] Specifically, another embodiment of the present invention provides a thin-layer overlay paving construction method comprising: a pretreatment step of removing foreign substances from a substrate surface; a pouring step of forming an adhesive layer by pouring an environmentally friendly epoxy-based thin-layer overlay paving material composition onto a substrate surface that has undergone the pretreatment step; a laying step of forming an aggregate layer by laying aggregate onto a surface that has undergone the pouring step; a first curing step of curing the substrate surface that has undergone the laying step; an aggregate removal step of removing excess aggregate from the substrate surface that has undergone the first curing step; and a second curing step of curing the substrate surface that has undergone the aggregate removal step.

[0075] The above pretreatment step is a process of removing various foreign substances, including water, dust, paint, and contaminants, using known means such as high-pressure washing or a high-pressure air gun to form a sound base surface on the cement concrete surface to be repaired. At this time, the above pretreatment step may be performed without cutting the surface.

[0076] The above pouring step is a process of preparing an environmentally friendly epoxy-based thin-layer overlay paving material composition according to one embodiment of the present invention, and then uniformly applying it to a substrate from which foreign substances have been removed using a known coating means.

[0077] The above laying step is a process of spreading aggregate on the poured surface using a method commonly used in the field. At this time, it is desirable to spread an excess amount of aggregate beyond the amount that can be adhered through the above-mentioned eco-friendly epoxy-based thin-layer overlay paving material composition so that as much aggregate as possible can be attached to the substrate surface.

[0078] The above aggregate is a polygonal particle having a moisture content of 0.2 weight% or less according to KS F 2550, an LA abrasion test of 20% or less according to KS F 2508, and a Mohs hardness of 6 or higher, and when measured by the sieve analysis method of the aggregate, it is preferable that 5 mm passes 100%, 2.5 mm passes 30 to 75%, 1.2 mm passes 0 to 5%, and 0.6 mm passes 0 to 1%.

[0079] The above first curing step can be performed by maintaining the substrate surface, which has undergone the laying step, for a certain period of time so that the aggregate settles and the environmentally friendly epoxy-based thin-layer overlay paving material composition adheres without being exposed. Specifically, it can be performed for 1 to 2 hours at room temperature (20 ℃) ​​and for 2 to 4 hours at low temperature (10 ℃ or lower).

[0080] The above aggregate removal step can be performed by removing aggregates that are not adhered to the substrate surface by an environmentally friendly epoxy-based thin-layer overlay paving material composition among the aggregates sprayed on the substrate surface after the first curing step. At this time, the above aggregate removal step (S5) may include a process of sucking up and cleaning excess aggregates using known cleaning means such as an air gun or a vacuum suction device.

[0081] The above second curing step is performed by maintaining the state with excess aggregate removed for a certain period of time, and can be performed for 1 to 2 hours at room temperature (20 ℃) ​​or for 3 to 5 hours at low temperature (10 ℃ or lower).

[0082] An environmentally friendly epoxy-based thin-layer overlay paving material composition and a construction method for a thin-layer overlay paving material using the same according to one embodiment of the present invention use an epoxy main component composed of ingredients harmless to the human body and suppress the generation of concrete waste caused by cutting the existing paving layer, thereby having the effect of being semi-permanent and environmentally friendly. In addition, an environmentally friendly epoxy-based thin-layer overlay paving material composition and a construction method for a thin-layer overlay paving material using the same according to one embodiment of the present invention improve the penetration of the paving material composition into the existing paving layer, thereby inducing integrated behavior between the existing paving layer and the overlay layer, and has excellent adhesion and flexibility, allowing it to be strongly adhered to the existing paving layer regardless of the behavior of the existing paving layer due to temperature and environmental changes, and has the effect of improving durability such as water resistance, abrasion resistance, freeze-thaw resistance, wear resistance, and slip resistance.

[0083] Although preferred embodiments of the present invention have been described in detail above, the present invention is not limited to the above embodiments, and various modifications are possible by those skilled in the art within the scope of the technical concept of the present invention.

[0085] [Preparation Example 1] Microcrystalline wax treated with kelp extract

[0086] 10 parts by weight of fresh kelp and 100 parts by weight of washing water (tap water) at 7°C were mixed, soaked for 4 hours, and then removed to produce fresh kelp with sodium removed. Subsequently, the fresh kelp with sodium removed was roasted at 80°C for 45 seconds to produce roasted kelp. Then, 40 parts by weight of microcrystalline wax and 2000 parts by weight of water were mixed with 100 parts by weight of the roasted kelp, extracted using an ultrasonic extractor (ultrasonic intensity 1200 W, stirring speed 50 rpm, 8°C), centrifuged at 4800 rpm for 10 minutes, and the supernatant was filtered using filter paper (filter 5A) to produce microcrystalline wax treated with kelp extract.

[0088] [Preparation Example 2] Microcrystalline wax treated with kelp extract

[0089] Microcrystalline wax treated with kelp extract was prepared by using a kelp ultrasonic extract prepared by the following method, in the same manner as Preparation Example 1 above.

[0090] 10 parts by weight of fresh kelp and 100 parts by weight of washing water (tap water) at 7°C were mixed, soaked for 4 hours, and then removed to produce fresh kelp with sodium removed. Subsequently, the fresh kelp with sodium removed was roasted at 80°C for 45 seconds to produce roasted kelp. Then, 40 parts by weight of microcrystalline wax and 2000 parts by weight of a mixed solvent were mixed with 100 parts by weight of the roasted kelp, extracted using an ultrasonic extractor (ultrasonic intensity 1200 W, stirring speed 50 rpm, 8°C), centrifuged at 4800 rpm for 10 minutes, and the supernatant was filtered using filter paper (filter 5A) to produce a kelp ultrasonic extract. At this time, the above mixed solvent used was a mixed solvent in which water, magnetized water, and marrubiin of Chemical Formula 2 were mixed in a weight ratio of 1:0.6:0.1.

[0092] [Examples 1 to 3 and Comparative Examples 1 to 2]

[0093] An environmentally friendly epoxy-based thin-layer overlay packaging material composition and a comparative composition were prepared by introducing the mixed epoxy-based main component and curing agent, with the components and content as shown in Table 1 below, into a vacuum-type forced mixing mixer and mixing.

[0094] Classification (Weight%) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Epoxy subject 72 72 72 72 72 weight part Base resin 100 100 100 - 100 weight ratio Bisphenol F-type epoxy resin 1 1 1 - 1 Trimethiopropane methacrylate - 0.15 0.15 - - Bisphenol A type epoxy resin - - - 100 - Castor oil glycidyl ether 45 45 45 45 45 Aliphatic epoxy resin 15 15 15 15 15 D-erythro-sphingosine 6 6 6 - - Cordycepin 4 4 4 - - Epoxy hardener 28 28 28 28 28 weight part di(4-aminocyclohexylmethyl)aniline 100 100 100 - 100 Cardanol - - - 100 - dihydrazide compounds Adipic acid dihydrazide 22 - 11 - - dihydrazide isophthalic acid - 22 11 - - N,N-bis(2,3-epoxypropyl)-o-toluidine 7 7 7 - - N,N'-bis(salicylidene)-1,3-propanediamine 3 3 3 - - Microcrystalline wax 5 5 [Manufacturing Example 1] 5 [Manufacturing Example 2] - - Aliphatic epoxy resin: Glycerol diglycidyl ether + Carboxylic acid glycidyl ether = 1:1 weight ratio

[0096] [Test Example]

[0097] The experiments below show the experimental results comparing the characteristics of the embodiments according to the present invention with those of Comparative Examples 1 and 2, so that the characteristics of Examples 1 to 3 according to the present invention can be more easily identified.

[0099] [Test Example 1]

[0100] After preparing the excellent environmentally friendly epoxy-based thin-layer overlay packaging material compositions of Examples 1 to 3 and the comparative compositions of Comparative Examples 1 to 2, the viscosity and flash point before curing were measured, and the tensile strength, tensile elongation, and elastic modulus were measured after curing for 7 days. The results are shown in Table 2 below.

[0101] item Test method Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Viscosity before curing (cps) KS M ISO 2555 1659 1634 1610 2760 2105 Flash point (°C) ASDM D3278 92 94 97 68 79 Tensile Strength (Mpa)_7 days KS F 3006 24 25 27 12 17 Tensile elongation (%)_7 days KS F 3006 52 56 60 20 31 Elastic modulus (Mpa)_7 days ASDM D695 486 462 423 986 953

[0102] As can be seen in Table 2 above, the environmentally friendly epoxy-based thin-layer overlay packaging material compositions of Examples 1 to 3 of the present invention, when compared to the comparative compositions according to Comparative Examples 1 and 2, were found to have excellent workability due to low viscosity, excellent thermal compatibility and stability due to a high flash point, excellent tensile strength and tensile elongation, and a low elastic modulus.

[0104] [Test Example 2]

[0105] On a plate, the environmentally friendly epoxy-based thin-layer overlay paving material composition and comparative composition prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were poured, aggregate was laid on top, and compacted and cured to form a thin-layer overlay paving material with a total thickness of less than 10 mm.

[0106] The physical properties of the environmentally friendly epoxy-based thin-layer overlay paving material compositions and comparative compositions prepared in Examples 1 to 3 and Comparative Examples 1 to 2, and the thin-layer overlay paving material prepared using the aggregates, were measured, and the results are shown in Table 3 below.

[0107] item Test method Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Drying shrinkage (length change rate (%) KS F 2424 0.02 0.01 0.01 0.45 0.29 Wear resistance (mm) ASTM C 779 0.03 0.04 0.02 0.52 0.35 Slip resistance (BPT) ASTM E 274, ASTM D 4060 and ASTM E 303 78 79 80 44 56 Adhesion strength (Mpa)_1 day ASTM C 1583 2.5 2.5 2.7 1.1 1.2 Adhesion strength (Mpa)_7 days ASTM C 1583 3.0 3.1 3.4 1.0 1.4 Adhesion strength (Mpa)_28 days ASTM C 1583 3.4 3.6 3.7 1.4 1.9 Compressive strength (N / ㎡)_1 day KS M ISO 679 34.1 35.6 37.2 29.3 30.2 Compressive strength (N / ㎡)_7 days KS M ISO 679 42.3 43.1 44.6 36.1 38.2 Compressive strength (N / ㎡)_28 days KS M ISO 679 57.3 58.2 60.1 46.4 48.2 Flexural strength (N / ㎡)_1 day ASTM C 580 17.0 17.2 17.5 13.7 15.4 Flexural strength (N / ㎡)_7 days ASTM C 580 18.4 19.0 19.2 16.6 17.0 Flexural strength (N / ㎡)_28 days ASTM C 580 20.5 22.1 23.2 16.7 17.8 Absorption rate (%) KS M ISO 62 0.03 0.02 0.01 0.35 0.21 Audience Rate (%) KS F 2561 90 92 94 62 70 Salt penetration resistance (coulomb) KS F 2711 0 0 0 556 114 Freeze-thaw resistance (%) KS F 2456 90 92 93 63 69 Thermal compatibility ASTM C 1583 Pass Pass Pass Pass Pass crack resistance AASHTO PP34-98 No cracks No cracks No cracks cracks No cracks Outdoor exposure weathering test KS M 5000;3231, Xenon Arc Exposure Test Method (WX-A (Method A)) No issues No issues No issues yellowing yellowing

[0108] As can be seen in Table 3 above, it was confirmed that the thin-layer overlay packaging material using the environmentally friendly epoxy-based thin-layer overlay packaging material composition of Examples 1 to 3 of the present invention has superior strength characteristics such as adhesion strength, compressive strength, and flexural strength, as well as resistance characteristics such as drying shrinkage, abrasion resistance, slip resistance, water absorption rate, rust prevention rate, salt penetration resistance, freeze-thaw resistance, crack resistance, thermal compatibility, and weather resistance against outdoor exposure, compared to the thin-layer overlay packaging material using the comparative composition according to Comparative Examples 1 and 2.

[0110] As explained above, those skilled in the art to which the present invention pertains will understand that the present invention may be implemented in other specific forms without altering its technical concept or essential features. Therefore, all embodiments described above should be understood as illustrative and not restrictive. The scope of the present invention should be interpreted as including all modified or altered forms derived from the meaning and scope of the claims set forth below and their equivalents, rather than from the detailed description above.

Claims

Claim 1 1) 40 to 80 weight% of an epoxy main component containing 100 parts by weight of a base resin containing an epoxy resin; 10 to 50 parts by weight of castor oil glycidyl ether; 1 to 20 parts by weight of an aliphatic epoxy resin; 1 to 10 parts by weight of D-erythro-sphingosine; and 1 to 10 parts by weight of cordycepin represented by the following chemical formula 1, and 2) 100 parts by weight of di(4-aminocyclohexylmethyl)aniline; 10 to 30 parts by weight of a dihydrazide compound which is adipic acid dihydrazide, isophthalic acid dihydrazide, or a mixture thereof; and 1 to 10 parts by weight of N,N-bis(2,3-epoxypropyl)-o-toluidine; An eco-friendly epoxy-based thin-layer overlay packaging material composition characterized by comprising 20 to 60 weight% of an epoxy curing agent containing 1 to 10 weight parts of N,N'-bis(salicylidene)-1,3-propanediamine and 1 to 10 weight parts of microcrystalline wax. [Chemical Formula 1] Claim 2 An eco-friendly epoxy-based thin-layer overlay packaging material composition according to claim 1, wherein the base resin containing the epoxy-based resin is a mixture of a bisphenol F-type epoxy resin and a methacrylate compound having three or more functions mixed in a weight ratio of 1:0.1 to 0.3; and wherein the methacrylate compound having three or more functions is one or more selected from the group consisting of trimethylolpropane methacrylate, pentaerythritol trimethacrylate, and pentaerythritol tetramethacrylate. Claim 3 In claim 1, the microcrystalline wax is a microcrystalline wax treated with kelp extract; the microcrystalline wax treated with kelp extract comprises the steps of: preparing raw kelp from which sodium has been removed by immersing raw kelp in washing water at 6 to 8 ℃ for 3 to 5 hours; and preparing roasted kelp by roasting the raw kelp from which sodium has been removed at 80 to 90 ℃ for 30 to 50 seconds. An eco-friendly epoxy-based thin-layer overlay packaging material composition characterized by being prepared by a method comprising the step of mixing 100 parts by weight of roasted kelp, 30 to 50 parts by weight of microcrystalline wax, and 500 to 5000 parts by weight of water solvent, and extracting under conditions of ultrasonic intensity of 500 to 2000 W, stirring speed of 20 to 100 rpm, and temperature of 1 to 20 ℃ to produce microcrystalline wax treated with kelp extract. Claim 4 An eco-friendly epoxy-based thin-layer overlay packaging composition according to claim 3, wherein the solvent is a mixed solvent comprising water, magnetized water, and marrubiin of Formula 2 mixed in a weight ratio of 1:0.5 to 1:0.1 to 0.3.[Formula 2] Claim 5 A thin-layer overlay paving construction method characterized by comprising: a pretreatment step for removing foreign substances from a substrate surface; a pouring step for forming an adhesive layer by pouring an environmentally friendly epoxy-based thin-layer overlay paving material composition according to any one of claims 1 to 4 onto a substrate surface that has undergone the pretreatment step; a laying step (S3) for forming an aggregate layer by laying aggregate on a surface that has undergone the pouring step; a first curing step for curing the substrate surface that has undergone the laying step; an aggregate removal step for removing excess aggregate from the substrate surface that has undergone the first curing step; and a second curing step for curing the substrate surface that has undergone the aggregate removal step.

Citation Information

Patent Citations

  • Construction method for exposed aggregate concrete pavement

    KR100895288B1

  • Ultra-thin pavement material composition including environmental friendly water borne epoxy resin, method of manufacturing and construction method of ultra-thin surface treatment pavement using this epoxy

    KR102172704B1